Proposed Community-Based Marketing Program for Lubricant Product X Case Studies on Scooter Clubs in Bandung - TRI WAHYUDI (NIM: 29107039), IMAM
The immensity of market potential growth of scooters has encouraged lubricant manufacturers to work on the segment more seriously by producing scooter-special lubricants. PT XYZ to bring Lubricant Product X to the market on September 7th, 2007. However, one of the challenges in launching a new product was the fact that consumers tend to be careful and restrain themselves in buying the product before actually witness its performance on a certain period of time. According to the Diffusion of Innovations Model (Everett M. Rogers, 2003), this situation was categorized as initial diffusion phase, in which the role of innovators and opinion leader were to be optimized in order to maximize sales. Therefore, PT XYZ needed to formulate a suitable marketing strategy to accelerate sales growth of Lubricant Product X to be able to support the company in dealing with fierce competition. This research proposed collaboration between innovators and opinion leaders, especially in scooters community, or known as Community Marketing. This research analyzed defining factors in building collaboration with the consumers' community, such as the characteristics of consumption behavior of scooters clubs community in Bandung area, in order to generate input for PT XYZ in a form of proposed community-based marketing strategy and the implementation for Lubricant Product X. It was also performing an explorative method by literature and field research, a direct in-depth interviews with respondents/informants, which were founders or members of the scooter clubs, with the total amount of 7 (seven) people from five scooter communities. Based on the data compiled on this research, the researcher conducted the processes of segmenting, targeting, and positioning on the scooter communities and decided the one which had the most potential to be involved in the Community Marketing Program. The Maticholic Club was chosen to collaborate with PT XYZ. In whole, this research developed an implementation plan of the Community Marketing Program for PT XYZ which was expected to contribute in the effort of winning the competition in the lubricants industry in Indonesia.